Characteristics and prenatal care utilisation of Romanian pregnant women. (June 2014) - Stativa, Ecaterina; Rus, Adrian V.; Suciu, Nicolae; Pennings, Jacquelyn S.; Butterfield, Max E.; Wenyika, Reggies; Webster, Rebecca
Abstract: Objective To describe the degree to which Romanian women access free prenatal care services, and to describe the demographic profile of women who are at risk for underutilisation. Methods Secondary data ( n = 914) were taken from a large, nationally representative sample of Romanian mothers and children ( N = 2117). Kotelchuck's Adequacy of Prenatal Care Utilisation Index was used to measure the adequacy of prenatal care. Results Seventy-eight percent of mothers underutilised prenatal care services. Those who did so to the greatest degree were likely to be young, members of an ethnic minority, poor, uneducated, and rural. Conversely, those who utilised care to the greatest degree were likely to be older, members of the ethnic majority, wealthy, educated, and city dwelling. Conclusion Despite the fact that many of the risk factors for underutilisation in this sample were similar to those found elsewhere in Europe and the developed world, these findings illustrate the worrisome magnitude of the problem in Romania, particularly among women with low levels of income and educational attainment. Future studies should examine factors that contribute to underutilisation, whether it corresponds to negative health outcomes, and whether targeted social interventions and outreach could help improve care.